Cardiac Myxoma: Typical Presentation but Unusual Histology - Hassan H. AlAhmadi; Noor Said Alsafwani; Mohamed A. Shawarby; Fayez Ahmed (Case Reports in Medicine)
Cardiac myxoma, a benign heart tumor, is the most common primary tumor of the heart. Glandular differentiation within these tumors is rare, occurring in approximately 3% of all cardiac myxomas. Its presence can complicate the diagnostic process. A 43-year-old Saudi male was referred with a two-month history of progressively increasing shortness of breath. Cardiovascular examination demonstrated a soft first heart sound with a plopping sound in the mitral area and a mid-diastolic murmur. A transthoracic echocardiogram revealed a large mass attached to the interatrial septum. A diagnosis of cardiac myxoma was made, and the patient underwent en bloc resection of the mass. Microscopic evaluation of the resected mass showed a neoplastic lesion with two components: first, a typical myxoma consisting of stellate and spindle cells in a myxomatous/hemorrhagic background; second, a glandular component consisting of separate, fused, and cribriform acini embedded within the myxomatous component. The acini were lined by a single row of columnar epithelial cells with basal nuclei and apical mucin. Occasional goblet cells were also identified. The postoperative period was uneventful, and on his recent follow-up in the clinic (nine months after the surgery), the patient is doing well with no complications. Herein, we emphasize the importance of accurately diagnosing such an entity, as it can be easily confused for a metastatic adenocarcinoma, especially in patients with a history of malignancy.